Sensitivity of a search for eV-scale sterile neutrinos with 8 years of IceCube DeepCore data. (8th September 2021) - Trettin, A.
Abstract: Several anomalies in reactor and accelerator neutrino experiments motivate the search for sterile neutrinos with squared mass splittings at the eV-scale. We present an analysis that probes the elements Uμ4 and Uτ4 of the extended (3+1) neutrino mixing matrix using an 8 year data sample from IceCube's DeepCore sub-array containing atmospheric neutrinos between 5 and 300 GeV. We show the expected sensitivities of the analysis to |Uμ4 | 2 and |Uτ4 | 2 under the assumption of mass splittings between 1 and 100 eV 2, and to |Uμ4 | 2 for mass splittings below 1 eV 2 . We specifically discuss how we overcame the challenges of efficiently calculating neutrino oscillation probabilities in the presence of very fast neutrino oscillations involving large Δ m 2 .